E-democracy – privacy-preserving, secure, intelligent e-government services : 7th International Conference, E-Democracy 2017, Athens, Greece, December 14-15, 2017, Proceedings /: 7th International Conference, E-Democracy 2017, Athens, Greece, December 14-15, 2017, Proceedings. (2017) - Unknown
No abstract available